Fungos micorrízicos arbusculares (FMA) em mangabeira (Hancornia speciosa Gomez, Apocynaceae) - Matos, Mara Rojane Barros (2007)
The present study aimed to evaluate and compare the diversity, abundance and frequency of AMF species in the rhizosphere of Hancornia speciosa Gomez trees in two wild populations, and to investigate the influence of the environmental variables on the AMF species abundance in both study sites. Sampling was performed in two sites. The first one, a “tabuleiro” area, presented a vegetation physiognomic similar to an open tree savanna, near to Alagoinhas, Bahia (12°08’ - 12°15’ S and 38°23’ - 38°30’ W). This site is 150 m high, with a plain to slightly plain relief, and wet to sub-humid climate, soils mostly acid, red-yellow alic podzols, of low fertility. The other study site was an area with a vegetation alike the shruby “restingas” (12°30’ - 12°32’ S and 41°23 - 41°27’ W), 5 km far from Lencois, 450 m high, with a tropical semi-wet climate and quartz sand soils, little developed, deep and excessively drained. Rhizosphere soil was sampled in the dry and rainy season in both study sites. AMF spores were extracted by wet sieving and centrifugation in sucrose, and prepared in microscopic slides to morphospecies characterization. Spore numbers counting were performed with the aid of a plate. Species diversity was assessed in the different sampling periods as well as before and after culturing with H. speciosa seedlings and with a mixture of Sorghum bicolor L. Moench e Crotalaria juncea L. Spore numbers were always higher in soils from Lencois than from Alagoinhas. In Lencois a significantly variation in spore numbers between the sampling periods was found, but not in Alagoinhas. No significantly correlation between spore numbers and rainfall within the sampling period was found (rs = 0.1957, p = 0.6423). In the present study no correlation between spore numbers and soil pH was found. Correlation between spore numbers and soil phosphor content was positive only in January 2005, in Alagoinhas (rs = 0.6335, p = 0.0492). Aluminum soil levels were negatively correlated with spore numbers in Lencois. No significantly correlation was found between spore numbers and root colonization rate in H. speciosa trees. Root colonization rate was always high (higher than 60%) in all periods, in both sites. A significantly negative correlation between mean temperature and minimum temperature and the root colonization rate was also found. Most frequent and abundant AMF species were Gl. etunicatum Becker & Gerdemann in Lencois, and Gl. etunicatum, Gl. macrocarpum Tulasne & Tulasne e Gl. Aff deserticola Trappe, Bloss & Menge in Alagoinhas, with a Constancy Index of 90 to 100% in both sites, and Relative Abundance above 10% of spore numbers. These species confirm the mycotrophic condition and may have a more important role on the root colonization. Species 51 richness and equitativity were higher in Alagoinhas than in Lencois, representing more uniform communities. Similarity between both sites varied from 76 to 83% in the diferente sampling periods. AMF species composition changes after culturing were not significantly. Only changes in the species spore numbers were observed. AMF species composition in field soils was very similar to the results obtained after culturing with the different trap plants used. Glomus etunicatum presented high sporulation when using H. speciosa as trap plant. Spore numbers was higher than the Most Probable Number (MPN) only in Lencois.